Green companions: Affordances of human-tree relationships - Vainio, Kaisa Kristiina; Takala, Tuomo; Limpens, Juul; Lummaa, Karoliina; Korrensalo, Aino; Räsänen, Aleksi; Tuittila, Eeva-Stiina (SPRINGER, 2025)
Trees offer multiple benefits, including impacts on physical and mental health. In this interdisciplinary study, we explored the relationships humans develop with specific favourite trees based on our survey data (n = 158) collected in the Netherlands. Here, we examined action possibilities (affordances) provided by trees, including immaterial actions, such as memorisation or the enjoyment of beauty. We implemented the affordance theory with mixed-method analysis. We identified three distinct types of human-arboreal relationships offering a different variety of action possibilities: nostalgic relationships, nurturing relationships, and empowering relationships. We assume that when humans form relationships with trees, the essence of trees is not their characteristics, but the possibilities for action. We recommend that urban green spaces would support interactions between humans and trees. By strengthening our connectedness with nature, it is possible to promote both human well-being and to strengthen environmentally responsible values and behaviours.